Relationship between Behavior of Traditional Medicines Usage and Health-Related Quality of Life in Surabaya Community in 2019 - Dewi Perwito Sari; Asti Rahayu; Digdo Suryagama (Health Notions, 2020)
The use of traditional medicine, in general, is considered safer than modern medicine. This study aims to determine the relationship between frequency of traditional medicines usage, the type and amount of traditional medicines consumed on traditional drug user's health-related quality of life.This research was an observational study conducted in a cross-sectional way. The study was conducted in the city of Surabaya in 2019. Calculation of sample size required for 400 people using the Slovin formula. Inclusion Criteria of respondents were domiciled in Surabaya, had or were taking traditional medicine, aged over 17 years. The research instrument was in the form of a Questionnaire and Short Form 6 Dimension (SF6D) sheet that had been validated for the measurement of the quality of life for health. The instruments were distributed using the Snowball Sampling technique with Google Forms. While manual distribution using random sampling techniques to the people of Surabaya.The collected data were analyzed with the Spearman correlation test and the Kruskal Wallis test. All analyses were carried out with the help of SPSS.The results show that the frequency, type and amount of traditional medicine consumed had a p>0.05 to health-related quality of life. The behavior of traditional medicine usage shows that there is no significant relationship to health-related quality of life to the health of the Surabaya community. Keywords: health-related quality of life; traditional medicine; SF6D; behavior